Surgical Treatment of Burst Fractures of the Dorsolumbar Spine by Short Segment Posterior Instrumentation. To Fuse or Not to Fuse?. Issue 1 (April 2016) - Koptan, Wael; El-Sharkawi, Mohammad; ElMiligui, Yasser
Introduction: The concept of 'Ligamentotaxis' using short segment posterior instrumentation and fusion is widely accepted for managing unstable burst fractures of the dorsolumbar spine. The aim of this work is to study the possibility of performing this procedure without fusion. Materials and Methods: This is prospective randomized study included 54 patients with burst fractures of the dorsolumbar spine treated with short segment posterior instrumentation without fusion (Group 1); compared with a similar group of 47 patients that were treated by the same technique with posterolateral fusion using iliac crest autograft. Patients were followed up for an average of 5y. Results: In Group 1, all patients with neurological impairment improved 1 to 2 Frankel grades; the VAS improved from an average of 7.8 to 1.3 and the overall complications were 4/54. The kyphotic deformity was corrected from an average of 22.6 degrees to an average of 3.1 degrees; the average anterior height of the fractured vertebrae was corrected from an average of 65% to an average of 92% and the compromise of the spinal canal improved from an average of 42% to 14%. Implant failure occurred in 2 patients. There was no significant difference in these parameters between Groups 1 and 2. In Group 2 there was significantly more operative time, blood loss, hospital stay and 10/47 complications including 2 implant failures. Conclusion: Short segment posterior instrumentation without fusion is a safe efficient procedure with significantly less operative time, blood loss, hospital stay and complications than when fusion was performed.